Investigating the relationship between plasma natriuretic peptide levels and chronic kidney disease stages in patients with and without concurrent heart failure - Umesh Kumar Pandey; Shivendra Singh; Uttam Kumar Singh; Nikhil Chaudhary (Heart India)
Background: Heart failure leads to ventricular stretch causing secretion of BNP and NT-pro-BNP from the ventricles into the circulation.Subsequently the clearance of BNP occurs via enzymatic degradation (Di-peptidyl peptidase-4 and neutral endopeptidase), and receptor binding, or via renal excretion, whereas NT-pro-BNP is mostly excreted by the kidneys.A standardized NT-pro-BNP cut-off threshold to diagnose HF has not been clearly recognized in CKD, as a chronic rise in NT-pro-BNP concentration could be due to injury to the myocardium or due to the decreased glomerular filtration rate. To assess and study the plasma concentrations of NT-pro-BNP among various stages of CKD, as well as among CKD patients with severe renal dysfunction and those with concurrent heart failure or without it. Materials and Methods: This cross-sectional study was conducted at the Institute of Medical Science, BHU, a tertiary care hospital at Varanasi, Uttar Pradesh. The study enrolled 99 chronic kidney disease patients who presented to us with symptoms of congestive heart failure at nephrology department.Laboratory investigations such as complete blood count complete metabolic Profile, NT-pro-BNP levels; urinalysis, 24-hour urine protein analysis, and 2D echocardiography were performed on all patients. Results: There is a notable co-occurrence of CKD and heart failure. Plasma NT-proBNP levels increases as the CKD stages advances, mainly in those with an eGFR below 60 mL/min/1.73 m² (stage 3 and above).In the present study, NT-proBNP concentration of 1860 pg/mL across all CKD patients with an eGFR below 90 mL/min/1.73 m² has a sensitivity of 70% and specificity of 71%. Meanwhile, a plasma NT-proBNP threshold value of 4400 pg/mL in our study is associated with a sensitivity of 90% and specificity of 70% in patients with an eGFR below 30 mL/min/1.73 m² for diagnosing heart failure. Conclusion: Plasma concentration of NT pro BNP varies with level of renal dysfunction and markedly elevation of concentration of NT-proBNP seen from CKD stage 3 onwards. The prevalence of heart failure increases as renal function deteriorates in individuals with CKD. The use of plasma NT-proBNP concentration is valuable for the evaluation of individuals who present with symptoms of congestive heart failure. However a stage based or eGFR based cut off should be used for analysis.